2013
DOI: 10.1371/journal.pone.0064144
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of an Nxf7 Knockout Mouse to Study NXF5 Deficiency in a Patient with Intellectual Disability

Abstract: Members of the Nuclear eXport Factor (NXF) family are involved in the export of mRNA from the nucleus to the cytoplasm, or hypothesized to play a role in transport of cytoplasmic mRNA. We previously reported on the loss of NXF5 in a male patient with a syndromic form of intellectual disability. To study the functional role of NXF5 we identified the mouse counterpart. Based on synteny, mouse Nxf2 is the ortholog of human NXF5. However, we provide several lines of evidence that mouse Nxf7 is the actual functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…We have previously shown that spatial learning in the Morris water maze was significantly impaired in Nxf7 KO mice (Vanmarsenille et al, 2013 ). Further analysis indicated that this lower performance in the mutant group was not caused by differences in path length (Figure 3A , F 1,409 = 2.72, P > 0.1), nor in swimming speed ( F 1,409 = 1.19, P > 0.1, data not shown), but apparently due to lower accuracy in their search for the hidden platform.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…We have previously shown that spatial learning in the Morris water maze was significantly impaired in Nxf7 KO mice (Vanmarsenille et al, 2013 ). Further analysis indicated that this lower performance in the mutant group was not caused by differences in path length (Figure 3A , F 1,409 = 2.72, P > 0.1), nor in swimming speed ( F 1,409 = 1.19, P > 0.1, data not shown), but apparently due to lower accuracy in their search for the hidden platform.…”
Section: Resultsmentioning
confidence: 95%
“…In the present study, we modeled the functional consequences of NXF5 deficiency (Jun et al, 2001 ; Frints et al, 2003 ; Grillo et al, 2010 ), using mice deficient for Nxf7 , the likely murine homolog of human NXF5 (Vanmarsenille et al, 2013 ). We examined the effect of genetic deletion of the nuclear export factor Nfx7 on a variety of behavioral tests and related the observed phenotype to changes in hippocampal synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations